2016
DOI: 10.1128/mbio.01516-16
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Susceptibility and Vaccine Protection Are Independently Controlled by Host Genotype

Abstract: The outcome of Mycobacterium tuberculosis infection and the immunological response to the bacillus Calmette-Guerin (BCG) vaccine are highly variable in humans. Deciphering the relative importance of host genetics, environment, and vaccine preparation for the efficacy of BCG has proven difficult in natural populations. We developed a model system that captures the breadth of immunological responses observed in outbred individual mice, which can be used to understand the contribution of host genetics to vaccine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 74 publications
8
94
1
Order By: Relevance
“…In line with this finding, the importance of host genotype for tuberculosis susceptibility and vaccine protection in the mouse model has been recently reported39. Thus, our results indicate that MTBVAC-vaccinated mice reactogenic for CFP10 and ESAT6 are more protected against tuberculosis than non-reactogenic strains.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this finding, the importance of host genotype for tuberculosis susceptibility and vaccine protection in the mouse model has been recently reported39. Thus, our results indicate that MTBVAC-vaccinated mice reactogenic for CFP10 and ESAT6 are more protected against tuberculosis than non-reactogenic strains.…”
Section: Discussionsupporting
confidence: 90%
“…Using an inbred recombinant mouse panel known as the ‘Collaborative Cross’ (REFS 134,135), Smith et al . 130 found that host susceptibility to TB and BCG vaccine efficacy were remarkably variable and genetically uncoupled from one another, such that protection to vaccination correlated with the intrinsic quality of the immune response.…”
Section: Figure 1 |mentioning
confidence: 99%
“…The architecture of (Marakalala et al, 2016) and animals (Gideon et al, 2015; Smith et al, 2016), and in a common form of TB granulomas, T cells are confined to the peripheral regions, while infected cells are in the central core (Figure 2) (Ernst et al, 2018; Kauffman et al, 2018). Since CD4 T cells must directly recognize and contact infected cells to control intracellular M. tuberculosis (Srivastava and Ernst, 2013), the architecture of TB granulomas may limit the efficacy of T cells in TB.…”
Section: Mechanisms Of T Cell Evasion In Tbmentioning
confidence: 99%